Bioethanol production from liquid pineapple waste using immobilized Saccharomyces Cerevisiae Var. Ellipsoideus in PVA-alginate-sulfate beads - Sarina Mat Rosid (Universiti Teknologi Malaysia, 2025)
Also available in printed version